1907 S.D. Sess. Laws 89, ch. 82, §§ 1-3. - (:unkn) unknown (General Publisher, 1907)
A person who, with intent to commit burglary, breaks and enters in the night time a building and commits or attempts burglary by the use of nitro-glycerine dynamite, gunpowder or any other high explosive, is guilty of burglary with explosives in the second degree.
--
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME